Density effects on nanoparticle transport in the hyporheic zone. (November 2018) - Jin, Guangqiu; Jiang, Qihao; Tang, Hongwu; Li, Ling; Barry, D.A.
Highlights: Numerical model validated by laboratory column and flume experiments on nanoparticles. Nanoparticles enhance density-driven flow effects. Trapping of nanoparticles within periodic bedforms is expected. Abstract: A carbon solution composed of nanoparticles ( d 50 = 85.7 nm) was used in experiments designed to explore nanoparticle transport characteristics within the hyporheic zone of a riverbed. Experiments and numerical simulations demonstrated that nanoparticle transport in the hyporheic zone is affected by hydraulic head gradients due to river flow-bedform interactions as well as density gradients associated with the nano-carbon solution. Differences with similar flow/transport situations were examined, and it was found that particulate-enhanced density can change hyporheic transport appreciably. In addition to density, particle settling enhances downward movement of the nano-carbon plume in the riverbed. While nanoparticle transport in the upper hyporheic zone is largely controlled by advection due to flow driven by head gradients at the bed surface, density gradients and particle settling influence the transport process significantly in the lower hyporheic zone. During the transport process, nanoparticles become deposited due to attachment to sand particles and filtration by small pores in the bed. Compared with transport where density variations are minimal, the particulate-induced density gradient induces downward transport of nanoparticles and entrained liquids, leading to deposition/accumulation at the base of the bed. Graphical abstract: